2019
DOI: 10.14639/0392-100x-2461
|View full text |Cite
|
Sign up to set email alerts
|

Towards a new staging of Ménière’s disease: a vestibular approach

Abstract: Ménière's disease (MD) is characterised by intermittent episodes of vertigo, fluctuating sensorineural hearing loss, tinnitus and aural pressure. Histopathologically, endolymphatic hydrops are seen initially in the cochlear duct and saccule, and with progression of the disease subsequent involvement of the utricle and semicircular canals occurs. The aims of this study are: 1) to assess the function of the saccule, utricle and three semicircular canals using cervical vestibular evoked myogenic potential (cVEMP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Further studies can assess if a dissociation between the 2 tests may be a peculiar characteristic of MD. Moreover, SVIN mainly detect a deficit of the lateral canal function; other tests, ocular and cervical VEMPs, are promising in studying macular function, above all when performed with sounds at different frequencies and studying the tuning curve of responses, thus allowing a mapping of all parts of the inner ear 28,29 . Some weak points in our investigation should be underlined.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies can assess if a dissociation between the 2 tests may be a peculiar characteristic of MD. Moreover, SVIN mainly detect a deficit of the lateral canal function; other tests, ocular and cervical VEMPs, are promising in studying macular function, above all when performed with sounds at different frequencies and studying the tuning curve of responses, thus allowing a mapping of all parts of the inner ear 28,29 . Some weak points in our investigation should be underlined.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that endolymphatic hydrops is observed most frequently in the cochlea and the saccule, followed by the utricle and semicircular canal. 20 With gadolinium-enhanced inner ear MRI, it is likely that the gadolinium injected into the tympanic cavity cannot evenly distribute to the distal parts of the ear, such as the semicircular canal, thus presenting false-positive endolymphatic hydrops. By contrast, intravenous gadolinium injection has a weaker signal but a more uniform distribution.…”
Section: Cho Et Al Applied the Evaluation Methods Introduced Bymentioning
confidence: 99%
“…Recent reports confirm that the otoneurological responses correlate well with the magnetic resonance imaging (MRI) showing that the EH starts from the saccule and then progresses to the SCC ( 6 ).…”
Section: Introductionmentioning
confidence: 73%